MODEL ON THE IMPROVEMENT OF INNOVATIVE BASED MARKETING PERSONNEL PERFORMANCE AT PT.BPR NUSAMBA CEPIRING - Tonny Frediyanto; Budhi Cahyono (IJIBE (International Journal of Islamic Business Ethics), 2017)
This study aims to examine the effect of learning orientation on innovative performance and its impact on the Marketing personnel performance with internal audit supervision as moderation. The problem of research is how to improve the marketing personnel performance through learning    orientation    and    innovative performance with internal audit supervision as moderation? The sample of this research is all marketing personnel who work in PT. BPR Nusamba Cepiring with a total of 101 respondents. Regression analysis is run with Statistical Package Social Science (SPSS) software to analyze the data. The result of the analysis shows that learning orientation has significant effect on innovative performance in improving the Marketing personnel performance by strengthening internal    audit    supervision. These    empirical    findings    indicate that learning orientation has a significant effect on innovative performance; learning orientation has a significant effect on the Marketing personnel performance; innovative performance has a significant effect on the Marketing personnel performance; and internal audit supervision can strengthen the effect of innovative performance on the Marketing personnel performance which also have a significant effect on team performance.Keywords : learning orientation, innovative performance, Marketing personnel performance and internal audit supervision